INNOVATION IN EDUCATION - Munir, Misbahul; Jazilurrahman, Jazilurrahman; Munif, Muhammad; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research was carried out to remember the importance of education in Islamic boarding schools in increasing Islamic boarding school innovation so that education in Islamic boarding schools is more active and implemented. By creating a professional educational atmosphere, new innovations are needed in education or ideas to achieve future educational targets existing Islamic boarding schools today, as well as being high quality Islamic boarding schools, By creating a professional working atmosphere, innovation is needed in the form of changing ideas or thoughts to achieve the future targets of the madrasah, as well as becoming a quality institution led by it. The head of the Islamic boarding school in managing his leadership includes providing direction and encouragement to his subordinates to carry out their duties and responsibilities. The aim of this research is to find out new innovations. The aim of this research is to find out the innovation of the head of the boarding school in improving the performance of administrators at the Ar-Rofi'iyyah Islamic boarding school and to find out how the management performs after making innovations at the Zainul Hasan Genggong Islamic boarding school.